Mathematical Creative Thinking Ability in Problem Solving Viewed From Adversity Quotient - Purwanto, Edi (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
This qualitative descriptive research aims to analyze the ability to think creatively mathematically in problem-solving in terms of the adversity quotient. The research was conducted on 10 students of the Mathematics Education Study Program, Faculty of Education, Pawyatan Daha University. Collecting data using questionnaires, tests, interviews, and documentation. Questionnaire to determine the Adversity Quotient scale. A test to measure the ability to think creatively mathematically. Data analysis in the form of induction and reduction theory. The results of the questionnaire showed 3 students (30%) quitters, 6 students (60%) campers, and 1 student (10%) climber. The test showed that 4 students (40%) had high ability, 4 (40%) moderate, and 2 (20%) low. The results of the analysis show that students with the quitter type fulfill the three problem-solving indicators. students of the flexibility criteria with the camper type fulfill all indicators but lack detail, and originality criteria students with the climber type are able to fulfill all problem-solving indicators in detail